Pengembangan Aplikasi Mobile Untuk Meningkatkan Minat Belajar Matematika Anak Berbasis Research and Development - Efriani, Laura; Sanjaya, Muhamad Rama; Paradina, Sevia; Pronika, Ginta; Angraini, Lisa; Ghifari, M. Farhan (Penerbit Widina, Widina Media Utama, 2025)
This study aims to design a mobile application as an interactive learning medium to increase children's interest in learning mathematics. The background of this research is the low level of interest and motivation to learn mathematics often found in elementary school-aged children. The application development method uses the Waterfall model, starting from the needs analysis stage, interface design, implementation, and testing. The developed application includes various features such as learning videos, interactive practice questions, and educational games based on mathematics. The study involved 40 elementary school students from grades 3 to 5. Based on the results of a 1–10 scale questionnaire, the average student learning interest increased from 5.0 to 8.2 after using the application. In addition, the average time spent studying mathematics increased by 128%, from 35 minutes to 80 minutes per week. Surveys showed that 65% of students preferred the educational games feature, followed by practice questions (20%) and learning videos (15%). User satisfaction was also high, with 95% of students and parents stating they were satisfied with the application. The test results indicate that the application can enhance children's engagement in learning math through a more enjoyable and less monotonous approach. With this application, it is expected to assist teachers and parents in providing a more engaging learning experience and improving children's understanding of mathematical concepts.ABSTRAKPenelitian ini bertujuan untuk merancang sebuah aplikasi mobile sebagai media pembelajaran interaktif guna meningkatkan minat belajar matematika pada anak-anak. Latar belakang dari penelitian ini adalah rendahnya minat serta motivasi belajar matematika yang sering ditemukan pada anak usia sekolah dasar. Metode pengembangan aplikasi menggunakan model Waterfall, mulai dari tahap analisis kebutuhan, desain antarmuka, implementasi, hingga pengujian. Aplikasi yang dikembangkan memuat berbagai fitur seperti video pembelajaran, latihan soal interaktif, dan permainan edukatif berbasis matematika. Penelitian melibatkan 40 siswa sekolah dasar dari kelas 3 hingga kelas 5. Berdasarkan hasil kuesioner skala 1–10, rata-rata minat belajar siswa meningkat dari 5,0 menjadi 8,2 setelah menggunakan aplikasi. Selain itu, rata-rata waktu belajar matematika meningkat sebesar 128%, dari 35 menit menjadi 80 menit per minggu. Survei menunjukkan bahwa 65% siswa paling menyukai fitur permainan edukatif, diikuti oleh latihan soal (20%) dan video pembelajaran (15%). Tingkat kepuasan pengguna juga tinggi, dengan 95% siswa dan orang tua menyatakan puas terhadap aplikasi. Hasil pengujian menunjukkan bahwa aplikasi dapat meningkatkan ketertarikan anak dalam mempelajari materi matematika dengan pendekatan yang lebih menyenangkan dan tidak membosankan. Dengan adanya aplikasi ini, diharapkan dapat membantu guru dan orang tua dalam memberikan pengalaman belajar yang lebih menarik serta mampu meningkatkan pemahaman konsep matematika pada anak.